Performance of a small diesel engine by experimental and numerical simulation analysis - Erdiwansyah; Leman, A. M.; Muhamad Norkhizan, Abdullah; Mulyadi, L.; Fitri, Khoerunnisa; Sardjono, R. E.; Maulana, M. I.; M. S. M., Sani (IOP Publishing, 2019)
A single cylinder diesel engine is an internal combustion engine; this machine is typically a compression ignition engine, fuel ignition through a high one made for compression of fuel and air mixtures. This study conducts a modelling with one dimension on a single cylinder four-stroke diesel engine and analyses the simulation results with experimental data. The simulation model covers the entire engine cycle consisting of compression, power, intake, and disposal for different engine speeds such as 1000, 2000, 3000, 4000, 5000, and 6000 rpm. Simulation modelling was done for the development of computation using software GT-POWER. The result of this modelling measures the accuracy level of machine parameter data from the modelled simulation. Based on the simulation results with modelling the machine, the data accuracy rate reached 90% in various cases tested with different engine speeds. Furthermore, the results also show that the modelling provides accurate data and can be used in the industry as a tool for development of different machines in the future.